Foodservice management in the Philippines - Perdigon, Grace P. (C & E Publishing, Inc., 2016)
Prescribed for students enrolled in foodservice degree programs and vocational courses, as well as those already employed in the foodservice industry, Foodservice Management in the Philippines provides an overview of the foodservice system and its elements. This book highlights the essential components and requirements in setting up and operating a foodservice institution that include material resources, personnel functions, equipment maintenance, budget control, sanitation and personal hygiene, and food preparation, cooking, and presentation. It also contains figures, illustrations, tables, and end-of-chapter summaries and teaching strategies to reinforce and check comprehension.